Influency factors in mathematical performance of first-year college students - González, Raúl (2000)
First year college students were assessed in three areas of mathematical competence: logical operational schemes, algorithmic and circle abilities and reading ability of mathematical problems. Group factors were analyzed and a profile developed between achievers and underachievers. Three needs common to both groups were identified: in formal logical operations, probabilistic, combining and distributive weaknesses; in calculus, weak metacognition due to poor anticipatory estimations, and in the reading of problems, difficulty finding the relevant statements.